KORELASI PENDAPATAN KELUARGA DAN PENDIDIKAN IBU TERHADAP PEMBERIAN ASI EKSKLUSIF - Faricha Kurnia Illahi; Yusuf Alam Romadhon; Yuni Prastyo Kurniati; Tri Agustina (Universitas Muhammadiyah Purwokerto, 2020)
Exclusive breastfeeding based on Government Regulation Number 33 of 2012 concerning Exclusive Breastfeeding isbreast milk that is given to babies from birth for six months, without adding and or replacing with other food ordrinks. Coverage of infants gets exclusive breastfeeding nationally at 61.33%. This figure has exceeded the 2017Strategic Plan target of 44%. The percentage of exclusive breastfeeding for infants 0-6 months in Central Java in2017 was 54.4%. Coverage of exclusive breastfeeding in Sukoharjo Regency is 60.36%.Thepurpose of this researchaims to determine whether there is a correlation between the level of family income and level of mother education ofexcluxive breastfeeding. This research use analytic observational design with cross sectional approach. Thepopulation in this study are mothers who have children more than six month in the working area of Gatak SukoharjoPublic Health Center. Sampling technique in this research using cluster random sampling technique. LogisticRegression test data obtained significance of family income level equal to 0.034 and mother education level equal to0.004.The limitation of this study is to collect data on the level of family income based only on interviews withoutany supporting questionnaireBased on these results indicate the correlation of family income level and mothereducation level of excluxive breastfeeding.